Fear of Missing Out (FoMO) and Learning Disengagement in College Students - Rahmah, Raudhatur; Afriani, Afriani; Aprilia, Eka Dian; Sulistyani, Arum; Amna, Zaujatul; Faradina, Syarifah (Gadjah Mada Journal of Psychology (GamaJoP), 2026)
Intensive smartphone use driven by fear of missing out (FoMO) is an early indicator of a student’s learning disengagement. Learning disengagement refers to students’ lack of engagement in the learning process due to distractions caused by smartphone use in the classroom. This research aimed to examine the relationship between FoMO and students’ learning disengagement. The sampling techniques used were multistage cluster sampling and disproportionate stratified random sampling, yielding a sample of 351 students (76 male and 275 female) from several public and private universities in Banda Aceh. Data were collected online and offline using the Learning Disengagement Scale and Online-Fear of Missing Out (ON-FoMO) Scale. Data analysis was conducted using Pearson’s product-moment correlation test. The findings indicate a positive relationship between FoMO and learning disengagement in students (r=0.606; p=0.000, p<0.05), suggesting that higher FoMO is associated with higher learning disengagement. The study indicates the need for strategic policies that require higher education institutions to implement smartphone use rules in class. This policy is important because it can improve students’ digital literacy, enabling them to distinguish between information relevant to academic activities.